3-Ethyl-4-[(E)-(4-fluorobenzylidene)amino]-1H-1,2,4-triazole-5(4H)-thione - Jeyaseelan, S. (International Union of Crystallography, 2012)
In the title compound, C(11)H(11)FN(4)S, the dihedral angle between the 1,2,4-triazole ring and the benzene ring is 25.04 (12)° and an intramoleuclar C—H⋯S interaction leads to an S(6) ring. In the crystal, inversion dimers linked by pairs of N—H⋯S hydrogen bonds generate R (2) (2)(8) loops.